2022
DOI: 10.1002/path.5857
|View full text |Cite
|
Sign up to set email alerts
|

5‐Alpha reductase inhibitors induce a prostate luminal to club cell transition in human benign prostatic hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) is a progressive expansion of peri-urethral prostate tissue common in aging men. Patients with enlarged prostates are treated with 5-alpha reductase inhibitors (5ARIs) to shrink prostate volume by blocking the conversion of testosterone to dihydrotestosterone (DHT). A reduction in DHT levels can elicit atrophy and apoptosis of prostate secretory luminal cells, which results in a favorable clinical response characterized by improved lower urinary tract symptoms. However, the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 38 publications
4
32
2
Order By: Relevance
“…Similar findings were recently reported in human benign prostate hyperplasia (BPH). Treatment with 5α reductase inhibitors, which are used to reduce intraprostatic androgen receptor signaling in BPH cells, was associated with a shift of luminal cells towards a Club-like identity [ 64 ]. In keeping with this, we and others have demonstrated that mouse LSC med -like luminal progenitor cells are intrinsically castration tolerant in both healthy and cancer contexts [ 5 , 9 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were recently reported in human benign prostate hyperplasia (BPH). Treatment with 5α reductase inhibitors, which are used to reduce intraprostatic androgen receptor signaling in BPH cells, was associated with a shift of luminal cells towards a Club-like identity [ 64 ]. In keeping with this, we and others have demonstrated that mouse LSC med -like luminal progenitor cells are intrinsically castration tolerant in both healthy and cancer contexts [ 5 , 9 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, we recently showed that the response to 5ARI treatment is highly variable. 8 Given the pleomorphic nature of BPH and the targeted killing of luminal epithelia by 5ARIs, we hypothesized that a higher stromal content may predict 5ARI failure. 4 Biopsies are not routinely performed for evaluating BPH histology, which means that noninvasive tests are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Current AUA guidelines recommend 5ARI treatment for patients with symptomatic BPH that display prostate volume ≥30 cc and PSA ≥1.5 ng/ml 6,7 . However, we recently showed that the response to 5ARI treatment is highly variable 8 . Given the pleomorphic nature of BPH and the targeted killing of luminal epithelia by 5ARIs, we hypothesized that a higher stromal content may predict 5ARI failure 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The development of a whole transcriptome panel for both human and mouse enables a wide range of translational, clinical, and basic biology research. For example, researchers have used WTA to identify focal changes in gene expression in kidney allograft rejection (Salem et al 2022), determine cell types affected by SARS-CoV-2 infection in the olfactory epithelium (Khan et al 2021), characterize functional gene expression differences across a heterogenous central nervous system tumor (Dottermusch et al 2021), and assess structure-specific responses to treatment in prostate hyperplasia (Joseph et al 2022). To promote these broad research applications, we have shown that WTA is compatible with a variety of tissue types and sample preservation methods (FFPE, fresh frozen, and fixed frozen).…”
Section: Discussionmentioning
confidence: 99%